Struma Ovarii: Imitating Malignant Ovarian Tumour Pre-Operatively (Delta Medical College Journal, 2025)
Struma ovarii is a rare variety of ovarian tumour that contain thyroid component accounting for 2-4% of ovarian teratomas. It usually presents as a unilateral adnexal mass at fifth and sixth decades of life. Majority of the cases are benign and can be managed by surgical excision. Malignant change is extremely rare. Pre-operative study combines ultrasonography, computer tomography scan and use of serum biomarkers in an attempt to differentiate from malignancy, because struma ovarii is a rare tumour with non-specific clinical presentation. Here we present a case of struma ovarii that presented with misleading findings pointing towards malignancy. A 38 years old lady, para 4+1, presented to us with an abdominal lump and occasional abdominal pain for 6 months. Her ultrasonography, as well as CT scan of whole abdomen findings suggested malignancy. The tumour markers like CA-125 and CA-19-9 were also elevated. Total abdominal hysterectomy with bilateral salpingo-oophorectomy along with infracolic omentectomy was performed. Struma ovarii was diagnosed by histopathology with negative cytology for malignancy. Due to vague clinical manifestation, elevated tumour markers and imaging characteristics, pre-operative diagnosis was challenging.Delta Med Col J. Jan 2022;10(1): 31-34